OPTIMIZATION OF NURSERY TECHNIQUES FOR SILVER POMPANO (Trachinotus blochii) IN BPBL BATAM: ANALYSIS OF GROWTH PERFORMANCE, SURVIVAL RATE, AND WATER QUALITY - Imanda Khalidah; Indra Lesmana; Rodhi Firmansyah (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Riau, 2025)
The production of silver pompano (Trachinotus blochii) in Indonesia has declined sharply, highlighting persistent issues in its nursery stage, particularly the inability to promote rapid growth and high survival rates when water quality fluctuates. This research assessed intensive nursery techniques implemented at Balai Perikanan Budidaya Laut (BPBL) in Batam by systematically testing different stocking densities, feeding schedules, and key water-quality metrics. Over a twenty-one-day culture cycle, observers collected data daily and interpreted it using descriptive statistics. Fish length rose from an initial mean of 2.50 cm to 3.73 cm, and mean weight climbed from 0.50 g to 1.30 g, yielding an average specific growth rate of 2.5% per day, a survival rate of 83.7%, and a feed-conversion ratio of 2.1. During the trial, temperature (27.6 °C), pH (7.81), dissolved oxygen (5.7 mg/L), and salinity (30 ppt) consistently fell within national SNI 7901-2013 standards. Most deaths occurred during grading rather than through cannibalism, indicating that handling stress, rather than predatory behavior, was the primary cause of loss. Collectively, these results establish a reference point for nursery management of T. blochii and furnish Indonesian aquaculture planners with data needed to boost fish-seed output while strengthening coastal community livelihoods